Antimicrobial Susceptibility of Phytoextraction in Combination with Antibiotics Against Bacteria Isolated from Diabetic Foot Infection - Asif, Rizwan; Ahmad, Hammad; Yasmin, Riffat; Ansari, Farheen; Mustafa, Madiha; Alam, Minhas; Shah, Subtain (International Health Review, 2024)
The worldwide growing antibiotic resistance against microbes has shifted the trend towards medicinal plants. Herbs are gaining courtesy for their effectiveness, safety, cheapness, and therapeutic potential. The current study focuses on the antibacterial potential of Mentha piperita (mint), Syzygium cumini (jamun), Citrus limon (lemon), and Punica granatum (pomegranate) extracts against isolated bacterial strains from diabetic foot infections. Diabetic foot samples (n=80) were collected for isolation of bacteria. Samples were run on respective media for isolation of different bacteria, which were further identified through microscopy and biochemical testing. Antibacterial activity was determined by disc and well diffusion methods. Several bacteria like S. aureus (42), P. aeruginosa (41), E. coli (28) K. pneumonia (22), S. epidermidis (15), Bacillus (7), and Proteous mirabilis (7) were isolated. Antibacterial analysis revealed moderate sensitivity of the four selected extracts against isolates, which was higher compared to most synthetic antibiotics. The lemon extract showed moderate antibacterial activity against S. epidermidis (8mm), P. aeruginosa (10mm) Bacillus (10mm), and P. mirabilis (11mm). Similarly, pomegranate also showed moderate sensitivity against all isolated bacteria. Jamun leaf extract showed antibacterial activity against S. epidermidis (12mm), K. pneumonia (10mm), E. coli (12mm), S. aureus, (11mm) and P. mirabilis (10mm). Hence plants could be used as an alternative to synthetic antibiotics with modifications to achieve better results.